2018
DOI: 10.1016/j.jpsychores.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

When is affect variability bad for health? The association between affect variability and immune response to the influenza vaccination

Abstract: Affect variability is related to immune response to an influenza vaccination and, in some cases, interacts with mean levels of affect. These oscillations in affective experiences are critical to consider in order to unpack the intricacies of how affect influences health. These findings suggest that future researchers should consider the important role of affect variability on physical health-relevant outcomes as well as examine the moderating effect of mean affect levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 50 publications
3
46
1
Order By: Relevance
“…Further, variation in PA related to daily stressors has been associated with peripheral inflammation (Sin et al, 2015). Research examining emotional variability or reactivity, or research utilizing a stress-buffering lens (e.g., Blevins et al, 2017; Jenkins, Hunter, Cross, Acevedo, & Pressman, 2018), may be needed to better understand the importance of PA on inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Further, variation in PA related to daily stressors has been associated with peripheral inflammation (Sin et al, 2015). Research examining emotional variability or reactivity, or research utilizing a stress-buffering lens (e.g., Blevins et al, 2017; Jenkins, Hunter, Cross, Acevedo, & Pressman, 2018), may be needed to better understand the importance of PA on inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature is relatively new and is focused on mental health (e.g., Gruber, Kogan, Quoidbach, & Mauss, 2013), we recently showed that PA variability is associated with a health-relevant physiological outcome: antibody response to vaccination. Specifically, we found that individuals who were both high in mean PA and high in PA variability had a lower antibody response to influenza vaccination than those who were high in mean PA but low in PA variability (Jenkins, Hunter, Cross, Acevedo, & Pressman, 2018). Thus, while average affect captures information meaningful for health, average dynamics of affect may also matter.…”
Section: Pa Measurement Considerationsmentioning
confidence: 95%
“…It might also change negative health behaviors, but generally, the mechanisms underlying why frequent ups and downs in affect might be harmful are unstudied. It is also beneficial to consider interactions between variability and mean levels of PA, with implications for health (e.g., Jenkins et al 2018a;Ong & Ram 2017). Further, novel approaches may be needed to deal with the possibility that certain types of patterning of PA (e.g., patterns of change that repeat) may matter (Jenkins 2017).…”
Section: Statistical and Design Considerationsmentioning
confidence: 99%